A framework for determining orthologues gene-drug targets based upon function, evolutionary selection rate, and physiological location - Staley, Joshua M. (Kansas State University, 2019)
The study of speciation, as a concept, existed prior to the elucidation of natural selection as the mechanism of evolution. However, speciation became a topic of scientific discourse starting primarily after the foundation of the modern synthesis. These disciplines operated independently; however, leading to the development of multiple theories of speciation. Some of the first efforts to consolidate speciation theory originated with the Biological Species Concept and the Modern Thesis, collectively introducing major factors of speciation (i.e. habitat, genealogy, evolutionary pressure, etc.) (1–3) To clearly define a species, a concise, reusable framework is urgently needed in the life sciences; specifically, translational and comparative medicine. Each of these fields depends on identifying suitable species to 1) develop a new treatment based on laboratory animal studies or 2) to take an existing treatment in humans and use it in animals. This is a major concern for pharmaceutical development research. The challenge of identifying a suitable species is complex due to a lack of a framework that allows for the comparison of species on the gene-gene level. Due to this complexity, gene-gene comparison is ignored which can lead to failure in a drug development trial. Subsequently, the cost to the development organization in both time and resources, and to society for lack of new and effective treatments, maybe great. With the proposed clearly defined, reusable framework, researchers would be able to find orthologues disease genes in animals ensuring that those genes are operating within the same cellular milieu and comparable physiology. For this reason, we have implemented a tool that calculates the evolutionary stability of the gene represented by the ratio 𝐾𝑎/𝐾𝑠. This ratio can be used to find conserved genes across multiple species and assist in the determination of whether that gene is a good candidate for drug targeting and in which species the gene exists. In order to meet the needs of researchers in the field; we began integrating GenBank, KEGG, and Refseq, with this tool, to allow those in the field to easily search across species.
Keywords: Speciation; Animal health; Human health; Genetics; Bioinformatics